Modelo IVE: metodología, mediciones y simulación de las emisiones de fuentes móviles en la ciudad de Lima - Perú - Lovera, Daniel (2004)
The IVE Model has been designed to evaluate environmental conditions of emissions from mobile sources operating in cities. So far, it is being succesfully applied in megacities such as Los Angeles, Santiago, Kajastan, Nairobi, among others, and in 2003 it was succesfully applied also in Lima, the City of Kings. For that purpose, institutional coordinations are made together with the Clean Air National Committee, in order to support this proposal set upon by Riverside University of California and Universidad de Chile. The IVE methodology is based on established protocols such as conduction characteristics, vehicles startings (VOCE units), fleet surveys and videos of the circuits chosen, which were carried out in a severe and technical way, thus obtaining valuable data for the following simulations of greenhouse gases, emission factors, the behaviour pattern of the whole of vehicles in the city, speed profiles, among others.We show some data collected during field work done in October-December, as well as an advance of the results obtained as compared with other megacities, where the IVE model has also performed measurements with the purpose of obtaining an accesible and cheap regional methodology, one that can allow to take mitigation actions in order to establish rules to improve citizens life quality.